Burung Lanskap Pedesaan di Wilayah Sukabumi Provinsi Jawa Barat - Assaf, Bilal Maulana; Kurnia, Insan (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Rural landscapes are part of man-made landscapes as a result of conversion of natural landscapes due to human needs. Birds respond positively to these changes as ecosystem components that are able to adapt and survive in rural landscapes. The countryside in the northern part of the Sukabumi is located between the natural landscape of Mount Gede and the rural landscape of Sukabumi City. The research aims to analyze the diversity of bird in the rural landscape of the Sukabumi Area. Research in the form of direct observation was carried out in February-May 2022. Bird data was taken using the point count method in the morning and evening. Qualitative analysis was carried out by describing and looking at the protection status. Quantitative analysis was carried out using (1) chi-square test, (2) Margalef Index (DMg), (3) Shannon-Wiener Index (H'), (4) venness index (E), and similarity index community (IS). There were 43 species of birds found from nine orders and 23 families. Five species birds are protected by the Indonesian Government. A total of 25 species (58%) are members of the Order Passeriformes. The majority are terrestrial birds, there is only one species that is considered a water bird, namely Von Schrenck’s Bittern (Ixobrychus eurhythmus). The DMg value obtained was 2.23-6.45, while the H' value obtained was 1.70-3.24, while the E value obtained was 0.74-09.90. The IS values obtained ranged from 0.24-0.58 with the highest similarity between the rice field habitat and the vegetable farm habitat.